Influence of Lithium on Structural Properties of Lead Zirconium Titanate (PZT) - A. Navakoti; D.S. Chakram; M. Dasari (Archives of Metallurgy and Materials)
Lead Zirconium Titanate (PZT) is a potential piezoelectric material for sensor and transducer applications due to its outstanding piezoelectric coupling near the morphotropic phase boundary (MPB). This is because PZT can switch between tetragonal and rhombohedral phases. PZT is still considered to be one of the piezoelectric materials that has received the greatest amount of attention from researchers and is used the most frequently. Modification with Lithium will improve the piezoelectric properties. In this study, the structural properties and morphological studies of Lead zirconium titanate and Lead zirconium titanate with Lithium modification have been evaluated. Various Scherrer’s models and other models, such as the Williamson-Hall model and Size-strain plots model, were used to display the observed fluctuations in crystallite size. Morphological analysis was used to determine the particle size. Graphs showing the distribution of particle sizes were drawn.